The Effect of THE EFFECT OF CARBON EMISSION DISCLOSURE ON FIRM PERFORMANCE MODERATED BY FIRM SIZE : A Study of Publicly Listed Firms in Indonesia - Widuri, Retnaningtyas; Andrew, Wilson; Widjieanto, Giordano Brandon (Riau International Conference on Economics, Business and Accounting, 2025)
ABSTRACT This study explores the influence of carbon emission disclosure on firm performance, with firm size as a moderating factor. In today’s climate of heightened awareness around environmental sustainability, companies are increasingly pressured to maintain transparency in reporting their carbon emissions. This research evaluates the effect of carbon disclosure on firm performance, measured by Tobin’s Q, and assesses whether firm size impacts this relationship. Data from 200 publicly listed firms, sourced from sustainability and annual financial reports, were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through WarpPLS, ideal for complex models with multiple constructs and indicators. Findings reveal a significant positive impact of carbon emission disclosure on firm performance, while firm size moderates this effect, indicating that environmental transparency supports performance improvements in firms of varying sizes. The study also identifies leverage and board size as positive contributors to firm performance, while age and board independence have minimal effects. These findings extend corporate sustainability insights and offer practical implications for policymakers and managers seeking to balance environmental responsibility with financial outcomes. Keywords: Carbon Emission Disclosure, Firm Performance, Firm Size, Sustainability